1998
DOI: 10.1002/(sici)1097-0134(19980401)31:1<61::aid-prot6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a stable mutant malic enzyme by introducing an extra ion-pair to the protein

Abstract: A double mutant (R9E/M17K) of pigeon liver malic enzyme with glutamate and lysine replaced for arginine and methionine at positions 9 and 17, respectively, was found to be much more stable in urea and thermal denaturation, but was enzymatically less active than the wild-type enzyme (WT). Unfolding of the enzyme by urea produced a large red shifting of the protein fluorescence maximum from 320 to 360 nm, which was completely reversible upon dilution. Analysis of the denaturation curves monitored by enzyme activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The N‐terminus of the enzyme, residues 23–31, has large contributions to the dimer interface, and smaller contributions to the tetramer interface. Our previous mutagenesis studies showed that these N‐terminal residues are important for the stability of the enzyme (Chou et al 1997Chou et al 1998; Huang et al 1998). In addition, residue Phe40 is important for the stability of the pigeon enzyme (Chou et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The N‐terminus of the enzyme, residues 23–31, has large contributions to the dimer interface, and smaller contributions to the tetramer interface. Our previous mutagenesis studies showed that these N‐terminal residues are important for the stability of the enzyme (Chou et al 1997Chou et al 1998; Huang et al 1998). In addition, residue Phe40 is important for the stability of the pigeon enzyme (Chou et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Over 20 years ago Perutz (Perutz and Raidt, 1975;Perutz, 1978) noted that salt bridges could potentially increase folding stability. Experimental studies on charge mutations have led to inconsistent conclusions on the contributions of charge-charge interactions to protein stability, and efforts to introduce stabilizing salt bridges have met with mixed success (Anderson et al, 1990;Dao-pin et al, 1991;Sali et al, 1991;Marqusee and Sauer, 1994;Waldburger et al, 1995;Meeker et al, 1996;Tissot et al, 1996;Spek et al, 1998;Vetriani et al, 1998;Huang et al, 1998;Ogasahara et al, 1998;Grimsley et al, 1999;Merz et al, 1999;Ramos et al, 1999;Giletto and Pace, 1999;Loladze et al, 1999;Perl et al, 2000;Pace, 2000;Spector et al, 2000;Strop and Mayo, 2000;Takano et al, 2000;Burkhard et al, 2000;Shaw et al, 2001;Perl and Schmid, 2001;Sanchez-Ruiz and Makhatadze, 2001;Olson et al, 2001;Kammerer et al, 2001;Loladze and Makhatadze, 2002). In contrast, in a number of theoretical studies based on continuum electrostatics, the view appears to have emerged that overall electrostatic interactions destabilize or marginally stabilize proteins and protein complexes (Novotny and Sharp, 1992;Hendsch and Tidor, 1994;Elcock, 1998;Elcock et al, 1999;Sheinerman et al, 2000;…”
Section: Introductionmentioning
confidence: 99%
“…In the structure-function relationship studies of pigeon liver malic enzyme, we have demonstrated the importance of Lys20 Lys3, Arg9, and Phe19 at the N-terminus of this enzyme for the Mn 2ϩ -l-malate binding and for the subunit association~Chou et al, 1996a, 1996b, 1997, 1998Huang et al, 1998!. The metal binding site of the enzyme was further characterized with metalcatalyzed oxidation~MCO!…”
mentioning
confidence: 99%